Water‐Based TiO2 Nanocrystal as an Electronic Transport Layer for Operationally Stable Perovskite Solar Cells. Issue 9 (5th June 2019) - Zhao, Yao; Han, Zhengyuan; Zhou, Wenke; Li, Qi; Fu, Rui; Yu, Dapeng; Zhao, Qing
Abstract : Halide perovskite solar cells (PSCs) provide a new opportunity for next‐generation photovoltaic applications. However, traditional low‐temperature solution‐processed TiO2 that acts as an electron transport layer for PSCs shows an inferior stability compared with solar cells based on high‐temperature (typically 500 °C) TiO2 ; however, the high‐temperature process is energy consuming and is not compatible with flexible device processing. Traditional TiO2 nanoparticles made from titanium tetrachloride dispersed in an organic solvent usually have many organic molecules attached on their surface that lead to the formation of deep‐level defect states during long‐term operations. Herein, environmentally friendly, water‐based Cl‐passivated TiO2 nanoparticles (W‐TiO2 ) are invented, and surface organic molecules are removed by a vacuum rotary evaporation process. W‐TiO2 ‐based PSCs can reach up to a 20.5% power conversion efficiency with reduced hysteresis and can maintain 80% of their initial performance after 500 h of continuous operation under 1 sun illumination at the maximum power point. This improved performance is ascribed to the organic‐molecule‐free and Cl‐passivated surfaces. The water‐based TiO2 nanoparticle dispersion also offers a convenient and universal way to introduce other passivation agents to further improve the photovoltaic performance of PSCs. Abstract : A water‐based TiO2 nanocrystal solution is developed to use as an electron transport layer for perovskite solar cells that show substantially reduced organic molecules and a high Cl content on the TiO2 nanocrystal surface, which effectively passivate the interface between TiO2 and perovskite layer with significantly reduced defects. Corresponding solar cells demonstrate a 20.5% power conversion efficiency and 500 h of operational stability.